Star Island : Skink #6 - Hiaasen, Carl (New York : Alfred A. Knopf, 2010)
Ann DeLuisa, body double for drug-addled pop star Cherry Pye, is kidnapped by an obsessed paparazzo, and Cherry's entourage must rescue her while keeping her existence a secret from Cherry's public--and from Cherry herself.
"This is a Borzoi book" --T.p. verso.
Keywords: Women singers -- Fiction; Paparazzi -- Fiction; Women singers -- Fiction; Photographers -- Fiction; Florida -- Fiction; Florida -- Fiction; Humorous fiction